Sclerotinia species in Serbia and possibilities of their control (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2023)
Sclerotinia species are economically important, necrotrophic and aggressive plantpathogens with a broad host range and worldwide distribution. They act as airborne orsoilborne pathogens, and can be transmitted by seed. These pathogens can affect cropsboth during the growing season and after harvest. Yield losses due to Sclerotinia diseasesin susceptible crops vary and may be as high as 100%. The most common pathogen fromthe genus Sclerotinia in Serbia is S. sclerotiorum. It occurs regularly on sunflower and itsincidence may exceed 50% in some years, thus causing economically important crop lossesin Vojvodina. Recently, two new species were detected in Serbia: S. trifolium in alfalfa andS. minor in lettuce plants. Diseases caused by Sclerotinia spp. are difficult to control due tothe long-term survival of sclerotia in the soil and development of airborne ascospores. Aswith many other diseases, there is no single treatment that can completely control thesepathogens. Implementation of multiple strategies, such as cultural practices (sanitation, croprotation and tillage), physical, chemical and biological protection, as well as deployment ofresistant cultivars, is necessary for effective disease management.
Keywords: plant-pathogenic fungi; Sclerotinia sclerotiorum; S. trifoliorum; S. minor; identification; plant disease control